FETOMATERNAL OUTCOME IN PATIENTS WITH THREATENED ABORTION IN A TERTIARY CARE CENTER IN SOUTH KERALA - Mammen, Kitty Elizabeth; VENUGOPAL, PRASANNA; S, ASIYA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Pregnancy complications due to threatened abortion are related with contrary pregnancy outcomes. The main aim of the present study was to analyze the changes in pregnancy outcomes among the women who experienced threatened abortion and normal pregnant control women. Methods: This retrospective observational study was performed among 117 pregnant women who were attending our Travancore Medical College Hospital, Kollam, during the period from January 2021 to January 2023 (2 years). The control group was developed from an equal number of asymptomatic women who were receiving antenatal care during the same period. Demographic parameters, clinical and ultrasound observations, treatment plans, and pregnancy outcomes were analyzed. Statistical Analyses: Data were analyzed using IBM SPSS Statistics. Results: Spontaneous abortion rate of 15.38% was observed with the threatened abortion group and control group as 5.1% (p=0.005). Women with threatened abortion had higher odds for placenta previa (p=0.048), pre-mature rupture of membranes (p=0.021), post-partum hemorrhage (p=0.001), and pre-term birth. Conclusion: Threatened abortion seems to be an important hazard to fetal survival and may intensify the threat for operational delivery.